Increasing the Agribusiness Competence of Pepper Farmers in the Border Area of West Kalimantan - Komariyati Komariyati; Endang Siti Rahayu; Mulyanto Mulyanto; Joko Sutrisno (Journal of The Community Development in Asia, 2022)
ABSTRACTThis study aims to formulate an extension model for pepper farmers to improve agribusiness competence. The research method uses quantitative. The population is farmers in 14 (fourteen) sub-districts of the West Kalimantan Border Region. The sampling technique used was multistage cluster sampling. The number of samples was 160 pepper farmers. Data collection techniques using questionnaires and documentation. The data processing and analysis technique used Structural Equation Modeling (SEM). The results of the study conclude that: First, to improve the competence of farmers, extension workers must pay attention to the level of formal education of farmers, the learning process, access to capital sources, and access to agribusiness facilities. Second, to improve the learning process, variables that need to be considered are farmer participation in community institutions and access to information sources. Third, to increase participation in community institutions, the variables that need to be considered are the level of formal education and motivation. Fourth, to increase motivation, the factor that needs to be considered is farming experience. Fifth, to increase access to agribusiness facilities, the variable to be considered is access to capital sources.Keywords: Competence, Learning, Education, Experience, Motivation, Participation, Access.